Prognozowanie poziomu życia ludności w Polsce - Sączewska-Piotrowska, Anna (Forecasting of Population's Life Level in Poland, 2006)
This paper is an attempt of calculation of the forecast of population's life level in Poland based on the synthetic variable. To carry out the analysis there were chosen diagnostic variables, their normalization was made and then, based on them, there was constructed synthetic measure. Based on this measure there was calculated trend function of synthetic variable, which allowed to calculate forecasts of population's life level in Poland for incoming years. Additionally the variables, which are describing population's life level, were divided to ten groups. For each group synthetic measure, trend function and forecasts was made too.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 295-304